Decentralizing Environmental Administration: A Common Law Approach - DE PAULA, Philip P. (Journal of Advanced Research in Law and Economics, 2016)
This paper intends to explore whether government regulation hinders rather than serves the goals of environmentalism by inhibiting possible free market mechanisms. The primary focus will be upon the tort aspects of environmental law, and whether these might be expanded to allow for litigation to serve as both the arbiter and the primary deterrent mechanism for environmental torts. In order to accomplish such a system, the viability of two current facets of environmental regulation will be examined. First, the imposition of environmental standards by centralized federal agencies will be examined to the extent that they limit efficiency and local responsiveness. The intention is to explore whether allowing state courts and local governments to administer environmental law will have the effect of opening up litigation and producing more reactive local results. Second, the institution of limiting standing to government actors, especially with regard to the Lujan decision will be examined as a mechanism that provides polluters a potential escape where government resources fail. Further, creating a generalized property right in environmental interests will be presented as a solution to the standing question. The aim is to determine the effect of centralized administration in preventing pollution control as well as presenting decentralization as a more effective and efficient means of pursuing this goal. Finally, the paper will present four suggestions for addressing some of the faults of the current regulatory system: empowering state courts to litigate environmental disputes to replace the federal regulatory system; loosening restrictions of standing; imposing a private damages regime; and applying strict liability to environmental claims. The paper will draw from United States jurisprudence on environmental law as well as drawing heavily from scholarly writing on environmental law and the economics of environmentalism.
Keywords: environmental law, environmental regulation, economics of environmentalism, decentralizing of Environmental Administration, Common Law, Free Market Environmentalism